-9(x-5)=x+22(2)

Simple and best practice solution for -9(x-5)=x+22(2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(x-5)=x+22(2) equation:


Simplifying
-9(x + -5) = x + 22(2)

Reorder the terms:
-9(-5 + x) = x + 22(2)
(-5 * -9 + x * -9) = x + 22(2)
(45 + -9x) = x + 22(2)

Multiply 22 * 2
45 + -9x = x + 44

Reorder the terms:
45 + -9x = 44 + x

Solving
45 + -9x = 44 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
45 + -9x + -1x = 44 + x + -1x

Combine like terms: -9x + -1x = -10x
45 + -10x = 44 + x + -1x

Combine like terms: x + -1x = 0
45 + -10x = 44 + 0
45 + -10x = 44

Add '-45' to each side of the equation.
45 + -45 + -10x = 44 + -45

Combine like terms: 45 + -45 = 0
0 + -10x = 44 + -45
-10x = 44 + -45

Combine like terms: 44 + -45 = -1
-10x = -1

Divide each side by '-10'.
x = 0.1

Simplifying
x = 0.1

See similar equations:

| 5.1+1.4n=2.16 | | 5v+4=-11 | | H(x)=x^2-3x-15 | | -63=7(x-9) | | 93+3x+18= | | -71-9m=82 | | 4x-4-24=0 | | (x-5y)(5x+y)=0 | | 4e-16+5e=29 | | 8x+6+7x+14= | | 6.3+0.5h=16.3 | | 1.6n+3.8n=54 | | 7.1x-2.8=24.18 | | 56=-8x | | -5y=-12 | | m+4=-3m | | (3x^2-5x-5)+(9x^2+2x+1)= | | 105x+112= | | X^2+0.02x-0.07=0 | | 6.3+0.5=16.3 | | 6(2-r)=15 | | 130+11x-2= | | .6p-.8=.6666p | | x+(-10)=45 | | 9m+4m+6=32 | | 27=5c-48 | | 110+19x-4= | | y+5=55 | | y=4+5x+x^2 | | 14+a=3a+2 | | 2-q=2+q+18 | | X-8.6=-5.1 |

Equations solver categories